Efficient in vitro generation of functional thymic epithelial progenitors from human embryonic stem cells - Su, Min (Sci Rep, 2015)
Thymic epithelial cells (TECs) are the major components of the thymic microenvironment for T cell development. TECs are derived from thymic epithelial progenitors (TEPs). It has been reported that human ESCs (hESCs) can be directed to differentiate into TEPs in vitro. However, the efficiency for the differentiation is low. Furthermore, transplantation of hESC-TEPs in mice only resulted in a very low level of human T cell development from co-transplanted human hematopoietic precursors. We show here that we have developed a novel protocol to efficiently induce the differentiation of hESCs into TEPs in vitro. When transplanted into mice, hESC-TEPs develop into TECs and form a thymic architecture. Most importantly, the hESC-TECs support the long-term development of functional mouse T cells or a higher level of human T cell development from co-transplanted human hematopoietic precursors. The hESC-TEPs may provide a new approach to prevent or treat patients with T cell immunodeficiency.